Portrait of Lady Bailey [3] ([195-?])
Part of a collection of portraits and photographs relating to Sir Kenneth Bailey, his family and career.
Condition: Good.
Title from inscription on reverse.
Inscriptions: "Lady Bailey" --In pencil on reverse.
Digital master available
National Library of Australia Manuscripts section MS 4622
National Library of Australia Pictorial section PIC/P776 Albums 665, 863, 976
Keywords: Bailey, Yseult, -- Lady, -- 1903-1980 -- Portraits